Looking In to the Changing Trend of Biological Risk Factors for Gall Stone Disease in Male and Female - Begum, Momtaz; Alit , SM Ashraf; Suhrawardy, SM (Journal of Chittagong Medical College Teachers' Association, 2015)
Conventional risk factors for Gall Stone Disease (GSD) are the five 'F's - Female, Fair, Fat, Forty and Fertile' but many study revealed changing trends particularly in age, multiparity and cigarette smoking particularly in Western countries. The etiology of cholelithiasis is considered to be a multi factorial, with interaction of genetic and environmental factors. Most exogenous factors are a consequence of westernization of modern societies, including a high intake of refined carbohydrates and a high prevalence of obesity, non-insulin dependent diabetes, atherosclerosis and sedentary life-style. From January 2011 to July 2014, consecutive patients who underwent Laparoscopic Cholecystectomy (LC) at Chittagong Medical College Hospital and Royal Hospital of Chittagong City were included in a prospective database targeting biological and biochemical characteristics in Male(n=256) and female (n=256). Data collected using predetermined approved case record form, including age, sex, demographic data, biochemical data before operation. The prevalence of diabetic was more among female where hypertension and dyslipidemia were more prevalent in males. Multivariate conditional logistic regression models revealed age is insignificant both in male and female (p=.088 vs. p=0.0744). Obesity is also insignificant (p=.091 in male, p=0.084 in female). Hypertension in both sexes (p= 0.02 in male,0.03 in female)diabetes mellitus in female (p=0.02) dyslipidemia particularly high serum LDL level particularly in female (p= 0.00001) is significantly related to gall stone. Metabolic factors like blood glucose level, dyslipidemia and hypertension may be closely related to the causation of gall stone disease. JCMCTA 2015 ; 26 (1) : 41-45